Sustainable Practices for Landfill Design and Operation - Townsend, Timothy G.; Powell, Jon; Jain, Pradeep; Xu, Qiyong; Tolaymat, Thabet; Reinhart, Debra (Waste Management Principles and Practice, 2015)
The management of municipal solid waste in many countries throughout the world has changed significantly over the past fifty years, with a shift from uncontrolled dumping or burning to complex systems that integrate multiple processes to recover materials or energy and provide containment to reduce environmental impacts. This volume, the first in the series Waste Management Principles, gives readers a comprehensive overview of advances in sustainable landfill design and operation. The authors developed this volume to serve as a tool for designers, regulators, and other parties interested in sustainable landfill practices and to be used in conjunction with fundamental design methodologies, location-specific regulations, new and emerging research results, and good engineering judgment. Dozens of graphs, figures, and tables provided throughout the text provide the designer with an excellent foundation to begin their analysis and apply the principles from this book to their site or facility.  In like fashion, operational experiences are provided throughout, tying in the important underlying fundamental concepts (e.g., accelerated gas production after liquids addition) to critical operational considerations (e.g., how to effectively collect the additional gas that is produced). The body of work presented here results from the development of bioreactor landfill design guidelines for the US Environmental Protection Agency's National Risk Manageme nt Laboratory, along with the combined knowledge and experience of the authors pertaining to sustainable practices for design and operation of sanitary landfills.  .